Study to modify the mechanical and chemical properties of building blocks (Thermostone) - A. Hamdi, Hamed; k. Hussain, Haleem; A. Hassan, Ayman (Iraqi Journal of Civil Engineering, 2017)
This study concern with a new technology to modified the compressive strength of the thermo brick which have a main role in construction field. This research using a new local cheap additives called (tar) which is available in Iraq (Kirkuk area). The experimental program have include three type of thermo brick available in local market (Iraqi, KSA, and Kuwaiti) and these type are common used in south area of Iraq especially Basrah City. The sample has exposed to the steam of tar in different temperature. Four affecting factor are studied carefully on compressive strength of brick including, tar , brick manufacture type, number of exposing faces of brick, and the age of brick after finishing expose of brick to the tar steam. The result shows maximum compressive strength conducted are 4.4 MPa when two faces expose to tar and two hours’ time of exposing ( one hour for each face) and the modified percentage was 62% compared with reference sample (KSA type). The improvement in compressive strength of Iraqi type and Kuwaiti were 27% and 45% respectively. Furthermore the improvement of compressive strength with same condition aforementioned but for one hour exposing time (half hour on each face) are 37.5%. The chemical properties also has conducted in this study.